A prospective study on clinical outcome of complicated external hernias - Shakya, VC; Agrawal, CS; Adhikary, S (Health Renaissance, 2012)
Background: External hernias are relatively simple diseases in themselves to treat; however, complications developing in them, such as irreducibility, obstruction and strangulation, may present as a life-threatening one. Objective: To study the characteristics of these patients and identification of risk factors that may predict development of these complications would help place the patient in a high-risk group and subsequent intervention. Methods: It is a prospective descriptive study in patients presenting to Surgery Department of BPKIHS, Dharan, Nepal with a diagnosis of complicated external hernias from December 2009 to July 2011. Results: There were a total of 63 patients including 53 males (84.1%) and 10 females (15.8%). The average age of the patients was 49.23+21.4 years (range 10 days-85 years). The average duration of hernia was 6.36+6.57 years (range 5 hours -30 years). The median duration of complications was 2 days (range 5 hours-15 years). There were 7 mortalities (11.11%). The morbidity rate was 33.33% (21 cases). Risk factors identified for mortality were age >65 years (p=0.004), inguinal hernias (p<0.001), presence of co-morbid diseases (p<0.001), presence of strangulation (p=0.007) and bowel resection (p<0.001); and for morbidities were type of hernia (p<0.001), presence of co-morbid diseases (p=0.013), and bowel resection (p=0.002). Conclusion: Elderly males with co-morbid diseases with inguinal hernia and with strangulation and needing bowel resection are most likely to die from more complications. Such patients when seen in the outpatient department should be given priority admission and taken up for early elective surgery. DOI: http://dx.doi.org/10.3126/hren.v10i1.6002 HREN 2012; 10(1): 20-26